HUBUNGAN KEPERCAYAAN DIRI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BIOLOGI - Nadhifa Fikri Amalia; Suharsono Suharsono; Ryan Ardiansyah (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
In the learning process, lack of self-confidence and learning motivation are factors that can affect student learning outcomes. The purpose of this study was to determine the relationship between self-confidence and learning motivation on student learning outcomes in biology subjects in Class XI MIPA SMAN 6 Tasikmalaya Academic Year 2020/2021. The method in this study used the correlational method with the population, namely all XI MIPA classes and a sample of two classes was selected using purposive sampling and selected 68 MIPA class XI MIPA 2 and XI 3 SMAN 6 Tasikmalaya students. The instrument used was a self-confidence questionnaire with 33 statement items and a learning motivation questionnaire with 27 statement items. Data were analyzed using statistical analysis correlation test product moment, simple regression and multiple regression. The results showed that (1) there was a relationship between self-confidence on learning outcomes with a correlation value of 0.403. (2) there is a relationship between learning motivation and learning outcomes with a correlation value of 0.285. (3) there is a relationship between self-confidence and learning motivation on learning outcomes with a correlation value of 0.430. So it can be concluded that there is a positive relationship between self-confidence and learning motivation on student learning outcomes.